Analytical and morphometric study of nutrient foramina of femur and its clinical implications - Dervisevic, Lejla; Dervisevic, Amela; Ajanovic, Zurifa; Hasanbegovic, Ilvana (International Journal of Research in Medical Sciences, 2019)
Background: The femur is supplied princially by the diaphyseal nutrient artery which enters the bone throught the nutrient foramen. This supply is essential during the growing period, the early phases of ossification, and in different surgical procedures. The aim of present study was to examine the morphology and topography of the femur nutrient foramen to provide detalied data on such features. Methods: This was a cross-sectional-descriptive study in which we observed 50 femurs. We analysed the number and location of nutrient foramina, the length of the bone, the position of the nutrient foramen regarding to values of FI, correlation between number of nutrient foramen and length of femur, correlation between position of nutrient foramen and side of extremity to which femur belongs. Results: The double foramina were common in right (57.1%) and left (42.1%) femur, mostly located in medial lip of aspera line in right (64.3%) and on the lateral lip in left femur (68.4%), with statistically significant correlation, χ = 4.85; p = 0.03, p <0.05. The foramina in left (89.5%) and right (96.4%) femur were commonly observed at their middle third, with no statistically significant correlation between position of foramen accordingly to Foraminal Index value and side of extremity on which femur belongs (p=0.56; p>0.05). There is positive correlation between length of right and left femur and number of foramina. Conclusions: The study provides data of the nutrient foramina on femur, which is helpful for clinicians to help preserve bone vascularization during surgery.